Green Microwave-assisted Synthesis of ZnO-Ag Nanocomposite using Clove Oil (Syzygium aromaticum L.) and Its Bioactivity against Staphylococcus aureus - Elvina Dhiaul Iftitah; Rizki Wahyu Aji Wibowo; Masruroh Masruroh; Khoirun Nisyak (The Journal of Pure and Applied Chemistry Research, 2020)
Microwave-assisted synthesis of zinc oxide-silver (ZnO-Ag) nanocomposite using clove (Syzygium aromaticum L.) oil has been investigated. Variation of solvents and irradiation time of microwave was studied. The product characterization was carried out using XRD, FT-IR, and SEM-EDS. The XRD analysis indicates ZnO-Ag nanocomposite has a polycrystalline structure. The ZnO peak was detected at 2θ = 31.99; 34.58 and 68.05, whereas the Ag peak was detected at 2θ = 38.36 and 44.49. The increasing of irradiation time reduces the crystallite size, and generally has size range between 9 and 12 nm. SEM-EDS confirmed the existence of the ZnO-Ag nanocomposite with percentage of Zn (46.89%), O (29.72%) and Ag (23.39%). Moreover, antibacterial evaluation on Staphylococcus aureus give the inhibition zone in 13.3 mm. This result slightly gives better activity than the reference.